Physiotherapy Counseling on Complaints of Foot Pain for the Women's Community at the Rampal Celaket Health Center - Ni Nyoman AMP Astawa; Moh. Ali Sahib; Kurnia Putri Utami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
From the screening conducted at the Rampal Celaket Health Center, it was found that 5 out of 7 women present had complaints of pain in the soles of their feet or called Plantar Faciitis but their knowledge about plantar fasciitis was still minimal. To educate the women's community about exercises to relieve the pain caused by Plantar Fasciitis, particularly about the causes of pain and how to perform independent exercises at home properly to reduce complaints, counselling sessions were held. The technique involves educating the community about foot pain-relieving exercises and using posters as counselling media. The community is also given pre- and post-tests in the form of questions to gauge the efficacy of the counselling given. The evaluation showed an increase in participant knowledge from 0% to 100% because counselling worked well and was simple for participants to understand. Counseling exercises can improve participants' understanding of plantar fasciitis or foot pain.